Finite element modelling of a nuclear containment structure subjected to high internal pressure. (June 2017) - Tavakkoli, I.; Kianoush, M.R.; Abrishami, H.; Han, X.
Abstract: The objective of this article is to investigate the response of a nuclear power plant containment structure to a much higher internal pressure that could be encountered during a severe accident. To predict the nonlinear response of the prestressed containment structure under internal pressure, finite element program ANSYS is employed. The major challenges for modelling prestressing tendon elements are to accommodate parameters affecting prestressing forces including prestressing losses. In this study, the prestressing tendons are modelled using discrete elements. This method is more appropriate to model the prestressing tendons when they are not located in a symmetrical fashion. The effects of prestressing system are added directly as initial strain on the prestressing tendons in the finite element model. The proposed approach enables capability of the finite element model to update the prestressing forces, and to accomodate the non-uniform losses of prestressing tendon forces. It is observed that the containment structure subject of this study meets the design requirement of the current standards. The containment structure behaves linearly in excess of 1.5 times the design pressure and the structural integrity limit for pressure capacity is estimated as 2.7 times the design pressure. Highlights: The effect of prestress losses are accurately modelled in the containment structure. Damage to the containment structure initiated well above the design pressure. The limit for pressure capacity of this containment is 2.7 of the design basis accident (DBA). The failure of the containment initiated at the dome near the apex.